UPAYA PENGANGGULANGAN PENYEBARAN ALIRAN SEMPALAN DI MAN MODEL GORONTALO - Badruzzaman Badruzzaman (EDUCANDUM, 2017)
The splinter stream has been accessed by madrasah students, hence the effort toovercome its urgent spreading to be done. This qualitative research bases theassumption on Bryan R Wilson's theory of New Religiuos Movement, revealing theoriginal groups or orthodoxy and small groups or sects.It is found that Gorontalo people have original groups that have reference tounderstanding, namely: harmony of faith, duty, worship, form of interpretation,religious activity, and tarekat. While small groups that have emerged type of:conversionist, revolutionary, manipulationist, and reformist. The people of Gorontaloand the madrasah MAN Model responded to the urgency of splinter flow prevention.Although there are no specific programmed activities, efforts to overcome the splinterflow in MAN Model Gorontalo have been integrated in the learning process bothintracurricular and extracurricular